A New Protocol to Detect Multiple Foodborne Pathogens with PCR Dipstick DNA Chromatography after a Six-Hour Enrichment Culture in a Broad-Range Food Pathogen Enrichment Broth. (2nd December 2013) - Hayashi, Masahiro; Natori, Tatsuya; Kubota-Hayashi, Sayoko; Miyata, Machiko; Ohkusu, Kiyofumi; Kawamoto, Keiko; Kurazono, Hisao; Makino, Souichi; Ezaki, Takayuki
Abstract : A quick foodborne pathogen screening method after six-hour enrichment culture with a broad-range food pathogen enrichment broth is described. Pathogenic factors of Salmonella enterica, Shigella spp., enteroinvasive Escherichia coli, and enterohemorrhagic E. coli are amplified with a cocktail primer and rapid polymerase chain reaction (PCR), which finishes amplification in 30 min. The PCR amplicon was differentiated with a dipstick DNA chromatography assay in 5–10 min. Starting from a four- to six-hour enrichment culture, this assay was finished within 45 min. Detection sensitivity of this protocol was less than 2.5 CFU/25 g for S. enterica and 3.3 CFU/25 g for enterohemorrhagic E. coli in spiked ground meat experiments.